Persepsi Guru IPA terhadap Filosofi Ki Hajar Dewantara: Pendidikan yang Memerdekakan: Science Teachers' Perceptions of Ki Hajar Dewantara's Philosophy: Liberating Education - Khefrianti, Syinta; Nahadi, Nahadi2; Anwar, Syaeful; Praginda, Wandy (Jurnal Filsafat Indonesia, 2024)
A liberating education is a student-centered education in which students are given as much opportunity as possible to develop their potential, talents and interests so as to achieve the goal of safety and happiness in life initiated by Ki Hajar Dewantara. This article aims to determine the views of teachers, especially science teachers involved in the Teacher Mover Program, regarding Ki Hajar Dewantara's philosophy and the practices that can be applied to students based on this philosophy from an ontological aspect. The research method used is descriptive qualitative. The research subjects were four teachers who were practical teacher in PGP. The research instrument was a questionnaire related to liberating education. The results showed that teachers have an understanding and principles related to liberating education in accordance with the philosophy of Ki Hajar Dewantara which in the learning process according to student needs, develops student potential and sides with students. In addition, teachers can also describe learning practices to students related to liberating education and there are even teachers who have implemented these learning practices.